Hitlerowska polityka zagraniczna w świetle publicystyki Kazimierza Czapińskiego (1933-1939) - Chmielewska, Lucyna (Acta Universitatis Lodziensis. Folia Historica, 2003)
The article attempts to show how Kazimierz Czapiński saw and commented the activity of Hitler’s diplomacy. Kazimierz Czapiński (1882-1941) was an activist of the Polish Socialist Party (PPS), a member of Parliament and an active journalist. As a socialist and democrat Czapiński opposed Nazism. He criticized Nazi policy of expansionism forwards the Central-East Europe. Since the Nazi Party (NSDAP) came to power in Germany (1933) Czapiński emphasized a war danger. He hoped Europe could avoid a new war by organizing a coalition of democratic states - Great Britain, France, Soviet Union and other stales. Since 1937 Czapiński had not seen Soviet Union as the ally of democratic states. He thought the anti-Nazi peaceful coalition could be consolidated because the United States would have more interest in European political situation. The German-Soviet Nonaggression Pact surprised Czapiński. He recognized it as a treacherous pact of two totalitarian states.